THE USE OF INFORMATION TECHNOLOGY IN EDUCATION: THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN ONLINE SYSTEMS - da Silva Junior, Sidimar Lopes (Seven Editora, 2025)
In a Brazilian educational context, it is not uncommon to see tools that improve and stimulate learning. This article aims to investigate the possible applications of Information Technology in education, focusing on the hypothesis that Artificial Intelligence (AI) can be effectively used to improve learning through online systems. The general objective is to examine and demonstrate how AI and other strategic technologies can improve education, such as their use in digital platforms and techniques like gamification. The specific objective is to conceptualize and explore the applications of AI in online systems and gamification for education, as well as to demonstrate how these tools can improve the learning experience and expand the reach of education. The methodology adopted is deductive, with a qualitative approach, justified by the social and academic relevance of the topic in the current educational landscape.DOI: https://doi.org/10.56238/sevened2025.030-049